High-Voltage Current-Controlled Analog Switches for Various Kinds of Application - Jankowski, M. (ХНУРЭ, 2011)
The Paper presents several high-voltage analog switch designs. All of them are current-controlled solutions, which make them highly resilient to high voltage drops of transmitted signals. Possible field of application for all presented structures is discussed.
Keywords: voltage transmission; current transmission; current-mode control; analog switches; hHigh-voltage circuits